Surface nanocrystallization of β-titanium alloy by ultrasonic shot peening. (2020) - Kumar, Pramod; Mahobia, G.S.; Chattopadhyay, Kausik
Abstract: A significant improvement in mechanical properties of metallic materials can be obtained through grain refinement via severe plastic deformation (SPD). The ultrasonic shot peening (USP) process is one of the SPD processes that has recently proven capability in producing ultrafine-grains at the surface of metals without affecting internal chemistry. The β-type Ti–13Nb–13Zr alloy presents very attractive mechanical properties and biocompatibility for applications in medical sector as orthopedic and dental implants. In this investigation, Ti–13Nb–13Zr alloy was subjected to USP treatment of various durations and a nanocrystalline layer of ∼100 µm thickness was developed. The microstructural changes were characterized by optical, X-ray diffraction (XRD) and transmission electron microscopy (TEM). XRD is used to analyze the grain size and the mean microstrain in the top surface layer. The TEM and XRD analyses have shown that after USP treatment the microstructure consists of nanograins. Compared to the un-shotpeened samples, the shotpeened specimens exhibit increase in surface hardness and roughness. With increase in USP duration there is 20% increase in microhardness.